Using The Internet As A Modern Communications Technology Tool And Its Role In Improving Health Services - Lacheheb, Aicha; Benfardjallah, Bakhta (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى الكشف عن دور تقنية الاتصال في تحسين الخدمة الصحية عبر الإنترنت ،وهي أكثر وسائل الاتصال الحديثة انتشاراً. اعتمادنا على المنهج الوصفي المستخدم على نطاق واسع في البحث الاجتماعي والبشري. لقد اعتمدنا على جمع البيانات على عينة من مقدمي الخدمات الصحية. النتائج: الإنترنت يساهم في تحسين الخدمة الصحية. كما لفتت انتباه عدد كبير من المرضى في المستشفى من خلال تواصل المرضى مع المؤسسة الصحية عبر المواقع الإلكترونية. يحترم المستشفى بعناية خصوصية وبيانات المرضى في عملية التواصل عبر الإنترنت. Abstract: This study aims to reveal the role of communication technology in improving the health service via the Internet, which is the most widely, used modern means of communication. Our reliance on the descriptive approach widely used in social and human research. We relied on data collection on a sample of health service providers. Results: The Internet contributes to improving the health service. It also drew the attention of a large number of patients in the hospital through the patients' communication with the health institution via the websites. The hospital carefully respects the privacy and data of patients in the process of communicating via the Internet.
مقال
Keywords: صحة ; تحسين ; الانترنت ; الاتصال ; حديثة; Health; Improving; Internet; Communication; Modern